Mutational Pathways and Trade-Offs Between HisA and TrpF Functions: Implications for Evolution via Gene Duplication and Divergence - Lundin, Erik; Näsvall, Joakim; Andersson, Dan I. (Frontiers in Microbiology, 2020)
When a new activity evolves by changes in a pre-existing enzyme this is likely to reduce the original activity, generating a functional trade-off. The properties of this trade-off will affect the continued evolution of both functions. If the trade-off is strong, gene duplication and subsequent divergence would be favored whereas if the trade-off is weak a bi-functional enzyme could evolve that performs both functions. We previously showed that when a bi-functional HisA enzyme was evolved under selection for both HisA and TrpF functions, evolution mainly proceeded via duplication-divergence and specialization, implying that the trade-off is strong between these two functions. Here, we examined this hypothesis by identifying the mutational pathways (i.e. the mutational landscape) in the Salmonella enterica HisA enzyme that conferred a TrpF-like activity, and examining the trade-offs between the original and new activity. For the HisA enzyme there are many different paths towards the new TrpF function, each with its own unique trade-off. A total of 16 single mutations resulted in HisA enzyme variants that acquired TrpF activity and only 3 of them maintained HisA activity. Twelve mutants were evolved further towards increased TrpF activity and during evolution towards improved TrpF activity the original HisA activity was completely lost in all lineages. We propose that, aside from various relevant ecological factors, two main genetic factors influence whether evolution of a new function proceeds via duplication—divergence (specialization) or by evolution of a generalist: (i) the relative mutation supply of the two pathways and (ii) the shape of the trade-off curve between the native and new function.